2007
DOI: 10.1016/j.jhse.2007.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Submaximal Effort in Power Grip by Observation of the Strength Distribution Pattern

Abstract: This study examined patterns of grip strength when maximal and submaximal effort are applied. Using a sensor glove, 50 healthy subjects performed two different power grips. Both maximal and submaximal gripping showed characteristic patterns of strength distribution that were independent of the degree of power applied. Significant differences were also noted in the strength distribution patterns, depending on whether the grip was performed at maximal, or submaximal, strength. The small finger plays a decisive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…This may suggest that the alternatehands method is a better representation of true test scores due to the rest period for the alternate hand, somewhat giving the hand a fresh start each time and likely producing more consistent performance. In support of this hypothesis, when examining muscle fatigue in fingers, one study found intermittent periods of complete rest reduced muscle fatigue (Gü lke, Wachter, Katzmaier, Ebinger, & Mentzel, 2007).…”
Section: Discussionmentioning
confidence: 94%
“…This may suggest that the alternatehands method is a better representation of true test scores due to the rest period for the alternate hand, somewhat giving the hand a fresh start each time and likely producing more consistent performance. In support of this hypothesis, when examining muscle fatigue in fingers, one study found intermittent periods of complete rest reduced muscle fatigue (Gü lke, Wachter, Katzmaier, Ebinger, & Mentzel, 2007).…”
Section: Discussionmentioning
confidence: 94%
“…This finding is similar to the view of different authors who acknowledged that hand strength is influenced by the position of the wrist and the integrity of the digits and their surrounding structures. 4,9,34,38 Li 34 showed that the optimal wrist position for maximum power grip is 20 extension and 5 ulnar deviation. Wrist position varies during precision grip, depending on the prehensile pattern that needs to be attained.…”
Section: Grip Strengthmentioning
confidence: 99%
“…These restrictions could be the result of extra-articular malunion since failure to restore the normal volar tilt of the radius is associated with decreased grip strength. 19 The study conducted by Gu¨lke et al 38 showed that the contribution of all the digits is important for grip strength. During maximal grip each digit contributes around 23% to 27% of the strength while during submaximal grip, the index, middle and ring digits contribute between 26% and 32% of the strength and the little digit contributes around 15%.…”
Section: Grip Strengthmentioning
confidence: 99%
“…Instrumenting the hand includes such techniques as gloves with discrete sensors [8,9] or with sensor strips inserted into glove fingers [10], sets of pressure matrices [10] or a pressure mat attached to the hand [11], and distinct sensors attached to the hand [12]. Instrumenting the contact surface to acquire phalangeal kinetics includes using discrete sensors attached at specific locations [6,1316], and covering the surface with a pressure sensitive mat or thin-film grid and applying either a manual [7,1721] or automated feature-based [5] segmentation of the pressure distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Gloves with a small number of individual sensors, and sensor matrices attached to the hand or a glove, have incomplete coverage of the contact area [10]; such methods often target data collection at the middle of each phalanx [8,9,12,1416] which could alter the pressure distribution or not record pressures which have been observed to deviate from the middle of the phalanx [22,23]. The thickness of gloves can impact grip force output and distribution [24]; sensors of non-trivial thickness may alter the pressure distribution [11,12].…”
Section: Introductionmentioning
confidence: 99%